Combined pulsed dye laser and Q‐switched Nd:YAG laser intraumatic facial tattoo removal: A case series. Issue 5 (10th September 2019) - Bonan, Paolo; Bassi, Andrea; Bruscino, Nicola; Schincaglia, Emiliano; Gavrilova, Maria; Troiano, Michela; Verdelli, Alice
Abstract: Traumatic tattoos can be treated with several methods, including mechanical and chemical devices. However, they are rarely used due to the high risk of permanent side effects such as scarring and depigmentation. Recently, laser devices, especially the Q‐switched (QS) laser and the pulsed dye laser (PDL), applied in combination, have achieved complete clearance of the lesions without any risk of side effects. Herein, we reported three cases of traumatic facial tattoos successfully treated with combined PDL and QS Nd:YAG laser.